2020
DOI: 10.1111/echo.14747
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid valve geometry in patients with functional tricuspid regurgitation: A three‐dimensional echocardiographic study

Abstract: IntroductionTricuspid valve (TV) has a complex anatomy causing some difficulties in echocardiographic evaluation. In this study, we sought to assess the geometry of TV in patients with functional tricuspid regurgitation (TR) by the implementation of 2‐ and 3‐dimennsional (2D and 3D) echocardiography.MethodsIn a case–control study, the geometrical features of TV were evaluated in forty patients with functional TR using echocardiographic examinations, and those data compared with twenty‐five age‐ and sex‐matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The majority of dilation occurred in the septolateral, or minor axis, corresponding to selective dilatation of the free wall of the right ventricle. These patterns are consistent with the geometric Notes: Geometric measurements of the tricuspid valve leaflets in an ex vivo porcine model in its non-diseased (control) and regurgitant (FTR) state as compared to published (clinical) TEE measurements by: a Karamali et al [11] (n=52); or b Florescu et al [12] (n=58). All results are reported as mean (standard deviation).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The majority of dilation occurred in the septolateral, or minor axis, corresponding to selective dilatation of the free wall of the right ventricle. These patterns are consistent with the geometric Notes: Geometric measurements of the tricuspid valve leaflets in an ex vivo porcine model in its non-diseased (control) and regurgitant (FTR) state as compared to published (clinical) TEE measurements by: a Karamali et al [11] (n=52); or b Florescu et al [12] (n=58). All results are reported as mean (standard deviation).…”
Section: Discussionsupporting
confidence: 75%
“…Abbreviation: FTR: Functional tricuspid regurgitation. Notes: Geometric measurements of the tricuspid valve annulus in an ex vivo porcine model in its non-diseased (control) and regurgitant (FTR) state as compared to published (clinical) TEE measurements by: a Karamali et al [11] (n=52); or b Ton-Nu et al [13] (n=75). All results are reported as mean (standard deviation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By allowing a more detailed assessment of the tricuspid valve and its subvalvular apparatus, 3D was found to be superior to 2D echocardiography in the evaluation of tricuspid valve pathology. [5,6] An en face view of the tricuspid valve leaflets from both the atrial and ventricular aspects can be obtained by 3D echocardiography, allowing the evaluation of all three leafl ets from the base to the tip, including the posterior leafl et. [7] We also found that interfering lead was a major contributor to post-implantation TR.…”
Section: Discussionmentioning
confidence: 99%
“…It can be divided into four main parts: antero- and posterolateral as well as antero- and posteroseptal [ 1 , 3 ]. The geometry of the TVA can be significantly altered by tricuspid regurgitation (TR) [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%